POLÍTICA MONETÁRIA E INFLAÇÃO NO BRASIL: pressões básicas e mecanismos de propagação do nível geral de preços entre 2000 e 2015. - SILVA, Anderson Nunes (2018)
During the 1980s in Brazil, prices rose exorbitantly, about 260% a.a. In order to "try" to solve this problem, in 1999 it was the turn of the Brazilian monetary initiative, an implementation of the Inflation Target Regime (RMI). However, this regime suggests that, in order to combat inflation, it is necessary to act in a very rigid manner, with high interest rates, which may have a negative effect on the level of economic activity. However, it is believed that the Brazilian subsidiary is controlled by the strategy of search for results and not demand, which may refute an idea that risks are the best remedies to contain inflation. In this sense, this paper aims to understand, based on the method used by Noyola Vásquez and Osvaldo Sukel, what is more important than the general level of prices in Brazil? above the two digits. To do this, divide this work into three parts, in which the first one shows the design of monetary policy and then there is a brief review of the literature on inflation, focusing on the works of Vásquez (2000) The Sunkel (2000). But, The Sims, Fixed the Existence to Variations Prilations to Currency Pressures, but the flag of propagation of inflation, that may be limit policies. anti-inflationary. Subsequently, the RMI is discussed, with emphasis on macroeconomic, institutional design, especially Brazilian, and some critics of RMI based on studies already performed. Finally, it is shown that it is more pressured from an implementation of the RMI, emphasizing the basic inflationary pressures on the processes of propagation. Thus, the evidence is a monetary policy based on the RMI needs to be revised, since it is a monetary regime with low interest rates. However, in the Brazilian case, inflationary pressures were taken by the basic exchange and administration costs and were not considered "exclusively in demand".